Immune regulation of ovarian development: programming by neonatal immune challenge - Sominsky, Luba; Sobinoff, Alexander P.; Jobling, Matthew S.; Pye, Victoria; McLaughlin, Eileen A.; Hodgson, Deborah M. (Frontiers in Neuroscience, 2013)
Neonatal immune challenge by administration of lipopolysaccharide (LPS) produces enduring alterations in the development and activity of neuroendocrine, immune and other physiological systems. We have recently reported that neonatal exposure to an immune challenge by administration of LPS results in altered reproductive development in the female Wistar rat. Specifically, LPS-treated animals exhibited diminished ovarian reserve and altered reproductive lifespan. In the current study, we examined the cellular mechanisms that lead to the previously documented impaired ovulation and reduced follicular pool. Rats were administered intraperitoneally either 0.05mg/kg of LPS (Salmonella Enteritidis) or an equivalent volume of non-pyrogenic saline on postnatal days (PNDs) 3 and 5, and ovaries were obtained on PND 7. Microarray analysis revealed a significant upregulation in transcript expression (2-fold change; p<.05) for a substantial number of genes in the ovaries of LPS-treated animals, implicated in immune cell signalling, inflammatory responses, reproductive system development and disease. Several canonical pathways involved in immune recognition were affected by LPS treatment, such as nuclear factor-κB (NF-kB) activation and LPS-stimulated mitogen-activated protein kinase (MAPK) signalling. Real-time PCR analysis supported the microarray results. Protein expression analysis of several components of the MAPK signalling pathway revealed a significant upregulation in the expression of Toll-like receptor 4 (TLR4) in the neonatal ovary of LPS-treated animals. These results indicate that neonatal immune challenge by administration of LPS has a direct effect on the ovary during the sensitive period of follicular formation. Given the pivotal role of inflammatory processes in the regulation of reproductive health, our findings suggest that early life immune activation via TLR signalling may have significant implications for the programming of ovarian development and fertility.